Who marries whom and intentions for second child: Using family decision-making power as mediator. - Yuan Dang; Xin Liu (PLoS ONE)
Interest in exploring fertility intentions, decisions, or the actual number of children through the perspective of assortative mating has been increasing; however, the mechanisms linking these variables remain unclear. Existing studies have shown that gaps in socio-economic resources between spouses shape intra-household decision-making patterns. Individuals who have the final-say power over homemaking exhibit more bargaining power in family fertility decisions. Based on the 2014 China Family Panel Studies, this research used latent class analysis to obtain the intra-household decision-making variable. A generalized structural equation model was built to examine this potential mediator. The findings reveal that family decision-making power helps to elucidate the relationship between the patterns of assortative mating and fertility intentions. Differences in couples' educational attainment are a key aspect in assessing "who" is in charge of the household. The desire for a second child was greater if husbands had the final say. Participants in marriages where wives held decision-making power reported a lower willingness to have a second child. The mediation effects of "husband-dominated" or "wife-dominated" decision-making were confirmed in hypergamous marriage. Indirect-only mediating effects were found in mid-educated homogamous partnerships and hypogamous marriages. Suppression effects were present in educational homogamy among highly educated individuals.